Aplikasi Bot Akademik BAAK STMIK Jakarta STI&K Platform Line Messenger Menggunakan Go Languages - Lusita, Melani Dewi; Hurnianingsih, Hurnianingsih; Rihyanti, Erni (Program Studi Teknik Informatika Universitas Pamulang, 2020)
BAAK Jakarta STMIK Campus STI & K or the Academic and Student Administration Bureau is a bureau that handles everything related to organizing teaching and learning activities at the STMIK Jakarta STI & K Campus. Problems with the services provided on the site include, among other things, class schedules, exam schedules, academic news, academic calendars, KRS (Study Plan Card) filling schedules and others. The method in this study uses the waterfall in designing BOT applications based on the Line Messenger platform. The results of this study are to facilitate and expand student access to obtain services from BAAK. Not only makes it easy to get information about academics at the STMIK Jakarta STI & K Campus, but also makes it easy to share that information with friends.